Determination of Iron in Foods by the Atomic Absorption Spectrophotometric and Colorimetric Methods - Siong, Tee.E; Choo, Khoor Swan; Shahid, Siti Mizura (1989)
A competitive study of the determination of iron in a wide variety of foods was carried out using the atomic absorption spectrophotometric (AAS) and phenanthroline colorimetric methods. A total of156foods, belonging to 8 food groups were studied. FOT each food (determined in duplicate), ash solution was prepared and an aliquot subjected to AAS analysis, while another aliquot was determined by the phenanthroline method. Mean values for duplicate analysis of each food determined by the two methods were tabulated according to food groups. Results obtained by the AAS and phenanthroline methods showed good general agreement, with a correlation coefficient of 0.987. Statistical analysis using paired t-test showed that fOT 5 food groups, there was no significant difference (P < 0.05) in Results given y the two methods. Although a significant difference was observed fOT the remaining 3 groups, the t-statistic calculated was just above the significance level. Recovery values given fly the two methods were satisfactory, and were not significantly different. Variance for the phenanthroline method was, however, slightly higher. Results of the study suggest that both methods can be used satisfactorily for the analysis of this mineral.